Study of feto-maternal outcomes of pregnant women with severe pre-eclampsia and eclampsia attending a tertiary care hospital of Kolhan region - Kar, Soumya R.; Srivastava, Anjali; Bara, Manju M.; Jha, Ela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Hypertensive disorders in pregnancy, particularly severe pre-eclampsia and eclampsia, are significant contributors to maternal morbidity and mortality, especially in developing regions. In India, these conditions are the third leading cause of maternal mortality. This study aims to evaluate maternal and fetal outcomes in women with severe pre-eclampsia and eclampsia in a tertiary care hospital serving Jharkhand’s Kolhan region, focusing on rural and tribal populations to understand demographic and clinical risk factors. Methods: This hospital-based, prospective cohort study was conducted from September 2022 to September 2024 at Mahatma Gandhi Memorial Medical College and Hospital, Jamshedpur, India. A total of 120 pregnant women diagnosed with severe pre-eclampsia (blood pressure ≥160/110 mmHg with organ damage) or eclampsia (seizures associated with pre-eclampsia) were included. Data on sociodemographic characteristics, clinical presentations, and outcomes were collected and analysed using descriptive and inferential statistics, with a p-value <0.05 considered significant. Results: Of the participants, 73.33% were from rural areas, 73.33% were tribal, and 40.83% were under 20 years of age. Severe pre-eclampsia was present in 61.7% of cases, while eclampsia affected the rest. High rates of maternal complications, including HELLP syndrome (20.83%), acute renal failure (15%), and postpartum hemorrhage (15%), were observed. Adverse fetal outcomes included low birth weight (43.33%), preterm births (69.17%), and NICU admissions (26.67%). Conclusions: Severe pre-eclampsia and eclampsia in Jharkhand’s Kolhan region disproportionately affect young, rural, and tribal women. Findings underscore the need for improved antenatal care, early diagnosis, and community health interventions to reduce maternal and neonatal morbidity in high-risk populations.